2021
DOI: 10.3389/fpsyt.2021.660810
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Psychopathy on Neurocognitive Domains of Impulsivity in Abstinent Opiate and Stimulant Users

Abstract: Background: Psychopathy and substance use disorders (SUDs) are both characterized by neurocognitive impairments reflecting higher levels of impulsivity such as reward-driven decision-making and deficient inhibitory control. Previous studies suggest that psychopathy may exacerbate decision-making deficits, but it may be unrelated to other neurocognitive impairments among substance dependent individuals (SDIs). The aim of the present study was to examine the role of psychopathy and its interpersonal-affective an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 121 publications
(210 reference statements)
0
14
0
Order By: Relevance
“…The data used in the current study were collected as part of another project on impulsivity among substance users in Bulgaria (i.e., Psederska et al, 2021). Participants were recruited via flyers placed at substance abuse clinics, therapeutic communities, social venues, as well as through the study's web page and Facebook page.…”
Section: Participantsmentioning
confidence: 99%
“…The data used in the current study were collected as part of another project on impulsivity among substance users in Bulgaria (i.e., Psederska et al, 2021). Participants were recruited via flyers placed at substance abuse clinics, therapeutic communities, social venues, as well as through the study's web page and Facebook page.…”
Section: Participantsmentioning
confidence: 99%
“…Impulsivity has long been considered a central feature of psychopathy (7,31). Studies reveal that both trait (7,(32)(33)(34)(35) and neurobehavioral domains (36)(37)(38)(39)(40)(41) of impulsivity are related to psychopathy. However, these studies largely employ different definitions and measures of impulsivity and psychopathy and have produced some conflicting findings.…”
Section: Psychopathy and Impulsivitymentioning
confidence: 99%
“…Inconsistencies across findings may be explained by the multidimensional nature of psychopathy, as the majority of the studies investigating the relationships between psychopathy and neurobehavioral impulsivity examined these associations only at the domain-level (i.e., PCL sum scores). However, several studies have accounted for the distinct psychopathy dimensions and reported that only the lifestyle and antisocial domains are associated with both risky and disadvantageous decision-making (36,58,59) and impaired response inhibition (40,60,61). In contrast, the interpersonal and affective dimensions of psychopathy were associated with higher inhibition capacity (40,60,61).…”
Section: Psychopathy and Impulsivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Although many factors contribute to recurrence of MADs, a possible key predictor is impulsivity ( Ahn et al, 2016 ; Vassileva and Conrod, 2019 ). Impulsivity is defined as a predisposition toward rapid, unplanned reactions to internal or external stimuli with diminished regard to their negative consequences to themselves or others ( Ahn et al, 2016 ; Psederska et al, 2021 ). It is considered a key etiological factor in current conceptualizations of substance use disorder (SUD).…”
Section: Introductionmentioning
confidence: 99%